Heavy Oil Residues: Application as a Low-Cost Filler in Polymeric Materials - Borisova, Yulia Yurevna; Minzagirova, Alsu M.; Gilmanova, Alfina R.; Galikhanov, Mansur F.; Borisov, Dmitry N.; Yakubov, Makhmut R. (Civil Engineering Journal, 2019)
Deposits of oil sands, bitumen, extra-heavy oil, and heavy oil appear in more than 70 countries all over the world and the fraction of oil recovered gradually increases. High content of poly-condensed high molecular weight oil components (PHMOCs), which may amount up to 50-60% depending on conditions of oil formation, is the main difference of heavy oil and bitumen from conventional oil. PHMOCs can lay the foundation for the preparation of a large number of valuable materials due to their structural manifold and their potential still not discovered to full extent. This work is devoted to the study of the effect of PHMOCs on properties of the composition materials prepared from polyethylene matrix. An «asphalt» – industrial product of deasphalting of tar, as well as asphaltenes and resins isolated from heavy oil, were used as a source of PHMOCs. HDPE and fillers were characterized using MALDI, FTIR, DSC and TGA. For the new composite materials we evaluated the physicomechanical properties, the thermal decomposition characteristics (by TGA), and the accumulation rate of carbonyl groups in the oxidized polymer (on FTIR). Studies of new composite materials showed that the introduction of filler in an amount of up to 4% in a polyethylene matrix does not lead to a significant change in the physicomechanical properties, but for a number of parameters they are improved. It also figured out that the addition of PHMOCs to polyethylene makes it unnecessary to stabilize the resulting compositions with stabilizers of thermal oxidative degradation. Results of experimental studies indicate that industrial residue - «asphalt» is a promising filler and low cost of this stock renders it perfect source for the industry of polymer materials.